Histochemistry: historical development and current use in pathology. (February 2014) - Riva, MA; Manzoni, M; Isimbaldi, G; Cesana, G; Pagni, F
Abstract We describe the history of the histochemical stains that contributed most to the development of modern pathology during the last two centuries. Histochemical stains are presented in a list, which provides the essential information about year, country and main use of each to enable the reader to follow the chronological and geographical history of histochemistry. In addition to the historical evaluation of histochemistry development, we investigate how many classical histochemical stains survive in a modern laboratory of pathology and how often they are used for diagnostic practice compared to immunohistochemical (IHC) techniques. A ratio of about one histochemical reaction to 13 IHC reactions was tabulated. Finally, our data make it possible to define different cultural approaches to the terminology of histochemical and IHC stains: the former were based on eponyms, which link the stain with the name of its inventor, while the latter use a more impersonal biological terminology.